Juan de Mairena / Antonio Machado ; edición de Antonio Fernández Ferrer - Fernández Ferrer, Antonio; Machado, Antonio (1875-1939) (Letras hispánicas; 240-241)
1° ed. (1986, vol. I-II) , 2° ed. (1993, vol. I) (1995, vol. II) | Contiene: Vol. I -- Vol. II